In vivo targeted-imaging of mitochondrial acidification in an aristolochic acid I-induced nephrotoxicity mouse model by a fluorescent/photoacoustic bimodal probe - Li Xu; Li Chen; Hongwen Liu; Xingwang Chen; Shenghang Zhang (Materials Today Bio, 2024)
Aristolochic acid I (AAI), a natural compound in aristolochia type Chinese medicinal herb, is generally acknowledged to have nephrotoxicity, which may be associated with mitophagy. Mitophagy is a cellular process with important functions that drive AAI-induced renal injury. Mitochondrial pH is currently measured by fluorescent probes in cell culture, but existing probes do not allow for in situ imaging of AAI-induced mitophagy in vivo. We developed a ratiometric fluorescent/PA dual-modal probe with a silicon rhodamine fluorophore and a pH-sensitive hemicyanine dye covalently linked via a short chain to obtain a FRET type probe. The probe was used to measure AAI-mediated mitochondrial acidification in live cells and in vivo. The Förster resonance energy transfer (FRET)-mediated ratiometric and bimodal method can efficiently eliminate signal variability associated with the commonly used one-emission and single detection mode by ratiometric two channels of the donor and acceptor. The probe has good water-solubility and low molecular weight with two positively charged, facilitating its precise targeting into renal mitochondria, where the fluorescent/PA changes in response to mitochondrial acidification, enabling dynamic and semi-quantitative mapping of subtle changes in mitochondrial pH in AAI-induced nephrotoxicity mouse model for the first time. Also, the joint use of L-carnitine could mitigate the mitophagy in AAI-induced nephrotoxicity.